2007
DOI: 10.1097/aud.0b013e31804793ac
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Higher Stimulation Rates in the Nucleus Research Platform 8 System

Abstract: The use of higher stimulation rates may provide benefit to some but not all cochlear implant recipients. It is important to optimize the stimulation rate for an individual to ensure maximal benefit. The absence of any changes in T- and C-levels or in tinnitus suggests that higher stimulation rates are safe for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
5
18
0
1
Order By: Relevance
“…The CNC test results are somewhat consistent with previous studies that used Nucleus devices with the ACE strategy (Vandali et al, 2000;Holden et al, 2002;Plant et al, 2007 andWeber et al, 2007). In these studies, monosyllabic word or consonant perception was not affected by the increasing stimulation rates.…”
Section: Speech Perception In Quiet and Noisesupporting
confidence: 81%
See 2 more Smart Citations
“…The CNC test results are somewhat consistent with previous studies that used Nucleus devices with the ACE strategy (Vandali et al, 2000;Holden et al, 2002;Plant et al, 2007 andWeber et al, 2007). In these studies, monosyllabic word or consonant perception was not affected by the increasing stimulation rates.…”
Section: Speech Perception In Quiet and Noisesupporting
confidence: 81%
“…Many of these studies reported large individual variability among subjects. Although the recent study by Plant et al (2007) found no significant group mean differences between higher rate and lower rate programs, five of the 15 subjects obtained significantly better scores with higher rates (2400 pps/ch & 10 maxima, or 3500 pps/ch & 9 maxima) compared to lower rates (1200 pps/ch & 10 maxima, or 1200 pps/ch & 12 maxima) for speech tests conducted in quiet or noise. Only two subjects obtained significant benefits in both tests using the higher set of rates, and the results were not conclusive because significant learning effects were observed in the study.…”
Section: Burstmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure 1 shows that due to a current spread in the cochlea and by using a single-channel rate of 900 pulses/s, an SGN can be exposed to an effective rate of 7200 pulses/s when stimulation is delivered by eight electrodes. Some studies have shown that subjects prefer high single-channel stimulation rates in the range of 1700 to 4000 pulses/s (Nie et al 2006;Verschuur 2005;Kiefer et al 2000;Loizou et al 2000), others demonstrated no benefit (Friesen et al 2005;Plant et al 2002;Weber et al 2007;Holden et al 2002;Plant et al 2007;Arora et al 2009), while other research indicates that low to moderate stimulation rates, i.e., 250 to 500 pulses/s, work best (Balkany et al 2007;Vandali et al 2000). Significantly, most of these studies report large variance between the performance of individuals as a function of the stimulation rate.…”
Section: Introductionmentioning
confidence: 99%
“…To adjust the optimal stimulation parameters of the CI for each patient, the programming of the speech processor must be performed periodically. In the programming, one can adjust the level of stimulation and speech processing strategies and make changes according to the needs of each patient (10) . In live programming (LP) sessions, a clinical history check and a survey of complaints are performed, as well as of tests whose results can pinpoint the needs of the new programming.…”
Section: Introductionmentioning
confidence: 99%